2010
DOI: 10.1007/s00417-010-1513-8
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural changes in myotendinous nerve endings induced by injection of botulinum toxin into the extraocular muscle

Abstract: Injection of botulinum toxin into the extraocular muscle induced ultrastructural changes in the myotendinous nerve endings. The possibility that those changes might diminish the proprioceptive abilities of the extraocular muscle should be considered when botulinum toxin is used for the treatment of strabismus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…23 Although botulinum toxin type A is often used as an alternative to eye muscle surgery for the treatment of strabismus, some morphological studies on extraocular muscles suggest that botulinum toxins induce ultrastructural changes in the myotendinous nerve endings and that these changes might diminish the proprioceptive abilities of the extraocular muscle. 67,68 Corsi et al 69 and Li and Shen 70 noted alterations in the receptor morphology while analyzing resected rectus muscle specimens from patients who had undergone surgery for concomitant strabismus. They suggested that deranged proprioceptive function contributed to the cause of the strabismus.…”
Section: Palisade Endingsmentioning
confidence: 99%
“…23 Although botulinum toxin type A is often used as an alternative to eye muscle surgery for the treatment of strabismus, some morphological studies on extraocular muscles suggest that botulinum toxins induce ultrastructural changes in the myotendinous nerve endings and that these changes might diminish the proprioceptive abilities of the extraocular muscle. 67,68 Corsi et al 69 and Li and Shen 70 noted alterations in the receptor morphology while analyzing resected rectus muscle specimens from patients who had undergone surgery for concomitant strabismus. They suggested that deranged proprioceptive function contributed to the cause of the strabismus.…”
Section: Palisade Endingsmentioning
confidence: 99%
“…Only a single study 49 has analyzed the effect of BoNT-A on palisade endings but experiments were done in adult cats, when palisade endings are already mature, whereas the present study was done in newborn kittens when palisade endings are developing. After BoNT-A treatment, palisade endings in adult cats exhibit changes at the fine structural level, including increase of structural proteins (neurofilament) in myelinated and unmyelinated axons, separation of the myelin sheath, and incomplete coverage of terminal varicosities with Schwann cells.…”
Section: Discussionmentioning
confidence: 99%
“…After BoNT-A treatment, palisade endings in adult cats exhibit changes at the fine structural level, including increase of structural proteins (neurofilament) in myelinated and unmyelinated axons, separation of the myelin sheath, and incomplete coverage of terminal varicosities with Schwann cells. 49 It is important to note, however, that terminal varicosities of palisade endings are usually incompletely covered by Schwann cells, 8 , 9 , 13 and this feature cannot be a consequence of the BoNT-A treatment. Thus, the neurotoxin-induced changes of adult palisade endings are probably less severe than claimed in the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…One may reason that it could take a longer time to change existing gait patterns that had been present for the extended duration of spasticity. Another possibility would be the need for the subjects to adapt to the reduced spasticity and also to the decrease in proprioceptive input after intramuscular BT‐A [38,39]. Nevertheless, regardless of stroke onset, most participants were able to show serial improvement of gait even after these possible changes.…”
Section: Discussionmentioning
confidence: 99%